(untitled) (American Journal of Islam and Society, 2005)
There is a tendency to equate liberal Islam with moderate Islam. Yet there are occasions when to be liberal demands a sense of outrage and rebellion. The causes of the political radicalization of Islam are different from the roots of theological conservatism. For decades, the Royal House of Saudi Arabia has been theologically conservative but not politically radical. Indeed, for a long time the monarchy in Riyadh was a classic example of how a Muslim regime could be politically pro-western without being culturally westernized. Was the Saudi regime politically moderate without being doctrinally liberal? This journal debate has been rich in trying to diagnose the nature of Islam’s radicalization, but relatively thin in diagnosing its causes. The best diagnosis of these causes in this collection comes from Graham E. Fuller: The Muslim world, feeling itself under siege, and with its sensitivities heightened by its witness of the struggle of Muslims right across the global ummah, is not currently operating in an environment conducive to either intellectual openness or to liberal and reformist thought. The Muslim world is simply hunkered down in a defensive and survivalist mode. Indeed, the forces of terrorism in the Muslim world must be brought to heel. But this will not happen unless we see a change in hegemonistic American policies, the explicit American embrace of Israeli right-wing policies in the occupied West Bank, and the linkage with American fundamentalist Christian attitudes. I have never heard the problem better formulated. Indeed, there are global causes of Islamic radicalism and global reasons why “Muslim terrorism” has gone international. One factor is the “Latin Americanization” ...